Concomitant cytotoxic effector differentiation of CD4+ and CD8+ T Cells in response to EBV-infected B cells - Tamura, Yumi; Yamane, Keita; Kawano, Yohei; Bullinger, Lars; Wirtz, Tristan; Weber, Timm; Sander, Sandrine; Ohki, Shun; Kitajima, Yasuo; Okada, Satoshi; Rajewsky, Klaus; Yasuda, Tomoharu (Cancers, 2022)
Most people infected by EBV acquire specific immunity, which then controls latent infection throughout their life. Immune surveillance of EBV-infected cells by cytotoxic CD4+ T cells has been recognized; however, the molecular mechanism of generating cytotoxic effector T cells of the CD4+ subset remains poorly understood. Here we compared phenotypic features and the transcriptome of EBV-specific effector-memory CD4+ T cells and CD8+ T cells in mice and found that both T cell types show cytotoxicity and, to our surprise, widely similar gene expression patterns relating to cytotoxicity. Similar to cytotoxic CD8+ T cells, EBV-specific cytotoxic CD4+ T cells from human peripheral blood expressed T-bet, Granzyme B, and Perforin and upregulated the degranulation marker, CD107a, immediately after restimulation. Furthermore, T-bet expression in cytotoxic CD4+ T cells was highly correlated with Granzyme B and Perforin expression at the protein level. Thus, differentiation of EBV-specific cytotoxic CD4+ T cells is possibly controlled by mechanisms shared by cytotoxic CD8+ T cells. T-bet-mediated transcriptional regulation may explain the similarity of cytotoxic effector differentiation between CD4+ T cells and CD8+ T cells, implicating that this differentiation pathway may be directed by environmental input rather than T cell subset.
Gesehen am 31.10.2022